Hukum Organisasi Publik : Strategi Peningkatan Akuntabilitas Pemerintah di Era Society 5.0 di Kota Bandung - Gantika, Soma (Faculty of Law, Universitas Pekalongan, 2024)
The study aims to identify legal strategies that can improve government accountability in the digital and high-tech era, Society 5.0 in Bandung City. This study analyzes how the legal principles of public organizations can be implemented effectively to face the challenges and opportunities in this era. This study uses a qualitative approach with a descriptive-analytical method. Data were obtained through in-depth interviews with government officials, academics, and legal practitioners, as well as through document studies related to public policies and regulations. The results of this study found that the Bandung City Government has implemented strategies to improve accountability by applying the principles of public organizational behavior based on technology and integrated data in the Society 5.0 era. Through policies that support transparency, public participation, and digitalization of services, as well as the implementation of public organization laws, Bandung aims to create an efficient, responsive, and inclusive government. However, significant challenges such as limited technological infrastructure, low human resource capacity, and cybersecurity threats still hamper the effective implementation of e-governance. Therefore, infrastructure improvements, intensive training, and clear regulations are needed to create more accountable and sustainable governance in the digital era